The Influence of Problem-Based Learning and Blended Learning on Students’ Creative Thinking Ability in Class XI SMAN Plus Riau Province Material Body Defense System - Desi Anggraini; Yustina Yustina; Febblina Daryanes; Mariani Natalina (Postgraduate, University of Mataram, 2023)
This research aims to analyze the effect of the Problem Based Learning model through Blended Learning on students' creative thinking skills. This research was conducted in class XI SMAN Plus Riau Province in the even semester of the 2021/2022 academic year. The research parameter is students' creative thinking ability, with 4 indicators, that is fluent thinking ability, flexible thinking ability, original thinking ability and elaborating thinking ability. Data were collected using test questions. The results of the study in the control class obtained an average value of 63.75 (less creative category) and an N-gain value of 0.13 (less effective category). In the experimental class, the average value was 77.63 (creative category), with an N-gain value of 0.43 (effective category). Of the four indicators in the control class and the experimental class, the highest indicator is fluent thinking with values of 67.50 and 80.00 respectively, while the lowest indicator in the control and experimental classes is obtained in elaboration thinking, with values of 60.00 and 75.55 respectively. Problem Based Learning model through Blended Learning has a positive effect on the creative thinking skills of class XI students of SMAN Plus Riau Province on the material of the body's defense system